A Tale of Three Dieulafoy Lesions: A Case Report and Review of the Literature - Amarnath, Shivantha (Cureus, 2020)
A Dieulafoy lesion (DL) is a rare cause of non-variceal upper gastrointestinal hemorrhage. It is a large submucosal artery that lies in close proximity to the mucosal surface without any evidence overlying superficial ulcers. DLs can be found anywhere within the gastrointestinal (GI) tract, but are frequently encountered within the stomach. Most cases documented in the literature only describe isolated, single DLs occurring within the GI tract. Herein, we describe an unusual case of an elderly female with a medical history of compensated alcoholic liver cirrhosis who presented with massive hematemesis and endoscopy unveiled three DLs within the gastric cardia as the source of hemorrhage. The bleeding was successfully managed using novel endoscopic modalities such as Hemospray (Cook Medical, Bloomington, IN). We also provide an updated literature review on the diagnosis, pathophysiology as well as recent advances in the management of DLs.